2011
DOI: 10.1523/jneurosci.1453-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GABAAR Monoliganded States on GABAergic Responses

Abstract: To reach the open state, the GABA(A) receptor (GABA(A)R) is assumed to bind two agonist molecules. Although it is currently believed that GABA(A)R could also operate in the monoliganded state, the gating properties of singly bound GABA(A)R are poorly understood and their physiological role is still obscure. In the present study, we characterize for the first time the gating properties of singly bound GABA(A)Rs by using a mutagenesis approach and we propose that monoliganded GABA(A)R contribute in shaping synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…The primary fast-acting target of GABA is the ionotropic GABA A R, and it is well-known to be involved in the inhibition of cellular activity, particularly through its increasing of inhibitory postsynaptic potentials (Petrini et al, 2011). This is in line with the notion that GABA A Rs within aversion interaction sensorimotor subregions may predict enhanced inhibition, as reflected by lower signal change differences from the interaction contrasts in individuals with higher GABA A R BPs.…”
Section: Modulation Of Shock Anticipation Activity By Sensorimotor Gasupporting
confidence: 61%
“…The primary fast-acting target of GABA is the ionotropic GABA A R, and it is well-known to be involved in the inhibition of cellular activity, particularly through its increasing of inhibitory postsynaptic potentials (Petrini et al, 2011). This is in line with the notion that GABA A Rs within aversion interaction sensorimotor subregions may predict enhanced inhibition, as reflected by lower signal change differences from the interaction contrasts in individuals with higher GABA A R BPs.…”
Section: Modulation Of Shock Anticipation Activity By Sensorimotor Gasupporting
confidence: 61%
“…both GABA binding sites renders the receptor inactive in the presence of GABA (Petrini et al, 2011). The db3a4b3a4 order of a4b3d receptors was proposed previously in a study employing atomic force microscopy imaging complexes between epitope-tagged receptors and antibodies in HEK cells (Barrera et al, 2008).…”
mentioning
confidence: 71%
“…These were a4(F63C), d(F74C) (both in loop D at the "-" interface of the extracellular domain), and d(T269Y) (T69Y in the second membrane-spanning domain). The mutations to loop D residues were made to test the contributions of a4 and d subunits to receptor activation by GABA (Petrini et al, 2011). The d(T269Y) mutation was used to confer resistance to picrotoxin (Gurley et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, several of the present observations raise the intriguing possibility that, in the presence of 2-AEMP, GABA-elicited receptor activation occurs only from a mono-liganded state (i.e., only one site occupied by GABA). Previous studies have shown that GABA A receptors can open from monoliganded as well as multiliganded states (Twyman et al, 1990;Jones and Westbrook, 1995;Petrini et al, 2011). In particular, Petrini et al (2011) have shown that monoliganded channels activate slowly and desensitize minimally by comparison with multiliganded channels.…”
Section: Discussionmentioning
confidence: 99%